Methods for enhancing the electrochemical properties of battery electrodes

The silicon-graphene gradient alternating structure was prepared through magnetron sputtering technology and doped with Cu, which solved the problem of cracking caused by volume expansion of the lithium-ion battery negative electrode material silicon material during charging and discharging, and achieved improvement of the conductivity and cyclic stability of the electrode.

CN119265528BActive Publication Date: 2025-03-14CHINA RAILWAY ELECTRIFICATION ENGINEERING GROUP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411803767.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The volume expansion of the negative electrode material of lithium-ion battery leads to cracking during charging and discharging, affecting the cycle life and stability of the battery.

Method used

Magneto-controlled sputtering technology is used to prepare the alternating structure of silicon-graphene gradient and doped with Cu. By alternately deposition of graphite and silicon layers, the internal stress is reduced during the annealing process, the diffusion transition between graphene and Si layers is improved.

Benefits of technology

It improves the conductivity and cyclic stability of the electrode, alleviates the stress deformation of the silicon layer during charging and discharging, avoids interlayer cracking, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of metal material plating, and in particular to a method for electrochemical enhancement of battery electrodes. This method uses a magnetron sputtering process to prepare an electrode structure, and obtains an alternating structure of graphene and silicon. Since the graphene surface area is huge, the bonding with the current collector and the silicon layer is better, and the conductivity and cycle stability of the electrode can be improved. Moreover, since the graphene molecular structure is a three-dimensional hollow structure, it has a large elastic modulus and can absorb the cyclic stress deformation generated by the silicon layer during the cyclic charge and discharge process. When preparing a multilayer structure, the sputtering power is gradually changed, and the transition gradient method can further alleviate the deformation while avoiding the tendency of interlayer cracking. When the Si layer is doped with Cu, the Cu atoms cause lattice distortion inside the Si silicon layer, generating sufficient defects such as dislocations and vacancies, providing a buffer space for subsequent deformation, and further improving the conductivity of the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal material plating, in particular to a method for enhancing the electrochemical properties of battery electrodes. Background Art

[0002] New energy has attracted much attention due to its clean, renewable and environmentally friendly characteristics, but there are still problems such as power supply stability and cost-effectiveness, which limit the large-scale application of new energy. Secondary batteries are currently the best choice for energy storage devices that can achieve continuous and stable power supply. They are also the most widely used energy storage devices. Their ability to effectively store and convert energy can meet people's growing energy needs and play an important role in production and life. There are many types of secondary batteries. Lithium-ion batteries, storage batteries, nickel-chromium batteries, etc. are all common secondary batteries. Among these secondary batteries, lithium-ion batteries stand out because of their environmental friendliness and excellent electrochemical properties. Good energy density and long cycle life enable lithium-ion batteries to cope with a variety of application scenarios, thus achieving a wide range of applications.

[0003] The key materials of the internal structure of lithium-ion batteries are composed of positive electrode materials, negative electrode materials, electrolyte materials and separator materials. The main function of positive electrode materials is to provide active lithium ions (Li + ); the main function of the negative electrode material is to store and release energy; the main function of the electrolyte is lithium ion (Li + ) conducts between the positive and negative electrodes; the main function of the separator is to prevent the positive and negative electrode materials from contacting and causing the battery to short-circuit. When the lithium-ion battery is charging, Li + Lithium ions are released from the positive electrode material and embedded in the negative electrode material after passing through the electrolyte medium. At the same time, electrons are transferred from the positive electrode to the negative electrode through an external circuit, converting electrical energy into storable chemical energy. When the battery is discharged, due to the potential difference between the positive and negative electrodes, lithium ions spontaneously escape from the negative electrode material and return to embed in the positive electrode material. At the same time, negative electrode electrons migrate back to the positive electrode through an external circuit, converting the stored chemical energy into electrical energy.

[0004] The negative electrode materials of lithium-ion batteries must meet the following conditions: low electrochemical reaction potential, strong lithium storage capacity, small change in voltage platform, high ion-electron conductivity, stable solid electrolyte interface membrane, low cost, simple preparation process, and environmental friendliness. Common negative electrode materials can be divided into carbon-based and non-carbon-based materials. The theoretical specific capacity of silicon-based materials is 4200 mAh·g -1, far higher than graphite, and with obvious advantages such as environmental friendliness, high abundance of earth elements, and easy processing, it is considered to be one of the most promising candidates for negative electrode materials and has attracted widespread attention. However, since silicon materials are prone to volume expansion, and the expansion deformation rate even exceeds 300%, the expansion and contraction stress generated during the charging and discharging process causes severe cracking of the silicon negative electrode, and then the battery accelerates to failure. The commercialization of silicon negative electrodes is subject to multiple obstacles. The best way to alleviate the above problems is to prepare silicon-carbon composite materials using high specific capacity silicon materials and high stability carbon materials.

[0005] There are many methods for preparing silicon-carbon composite negative electrode materials, including chemical vapor deposition, mechanical ball milling, spraying, magnesium thermal reduction, sol-gel, and pyrolysis. The spraying method has the disadvantages of high energy consumption and high instrument requirements; the magnesium thermal reduction method has the disadvantages of low discharge specific capacity; the sol-gel method has high cost; the pyrolysis method has the disadvantages of poor dispersion performance and serious agglomeration; the negative electrode material obtained by mechanical ball milling has a short service life; the raw materials used in chemical vapor deposition are toxic and flammable.

[0006] On this basis, the present application adopts magnetron sputtering technology to alternately prepare silicon-graphene gradient electrodes and dopes Cu, thereby overcoming the disadvantages of the preparation method in the prior art and improving the electrochemical performance of the electrode. Summary of the invention

[0007] A method for enhancing the electrochemical properties of a battery electrode comprises preparing a silicon-graphene gradient composite electrode by magnetron sputtering and doping the electrode with metal Cu.

[0008] First, the current collector is cleaned and dried, and then placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 8-12sccm. The current collector is PET, PP, PI or PC.

[0009] Then, a Si-graphene gradient alternating structure is prepared. The target materials used are a silicon target with a purity of 99.999%, a graphite target with a purity of 99.999%, and a Cu target with a purity of 99.999%. The sputtering power of the silicon target is 80-100W, the sputtering power of the graphite target is 80-100W, and the sputtering power of the copper target is 20-30W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 15-25nm, and then the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to the preset value, and a 15-25nm thick Si layer is sputtered; the multilayer structure of the graphite layer and the silicon layer is alternately deposited in the above manner, and a gradient transition is achieved.

[0010] Finally, the alternating multilayer structure electrode was annealed to convert graphite into graphene, further reduce the internal stress generated during the sputtering process, and further improve the diffusion transition between graphene and Si layer. The background vacuum during annealing was 3.0×10 -4 pa, annealing at 300-400℃ for 20-30 minutes, and then naturally cooling to room temperature in vacuum to finally obtain a battery electrode with enhanced electrochemical properties.

[0011] The present invention firstly adopts a magnetron sputtering process to prepare an electrode structure, and obtains an alternating structure of graphene and silicon. Since the graphene surface area is huge, the bonding property with the current collector and the silicon layer is better, and the conductive performance and cycle stability of the electrode can be improved. Moreover, since the graphene molecular structure is a three-dimensional hollow structure, it has a large elastic modulus and can absorb the cyclic stress deformation generated by the silicon layer during the cyclic charge and discharge process. In addition, the sputtering power is gradually changed when preparing the multilayer structure, and the transition gradient method can further alleviate the deformation while avoiding the tendency of interlayer cracking. When the Si layer is doped with Cu, the Cu atoms cause lattice distortion inside the Si silicon layer, generate sufficient defects such as dislocations and vacancies, provide a buffer space for subsequent deformation, and further improve the conductive performance of the electrode. DETAILED DESCRIPTION

[0012] Embodiment 1:

[0013] A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 100W, the sputtering power of the graphite target is 100W, and the sputtering power of the copper target is 30W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 25nm. Then, the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 100W and 30W, and a 25nm thick Si layer is sputtered; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350℃ for 25 minutes, and then cooled naturally to room temperature in a vacuum state after annealing, finally obtaining a battery electrode with enhanced electrochemical properties.

[0014] The negative electrode of the battery was obtained by the above process, and the positive electrode used a lithium sheet. A three-component mixed solvent EC∶DMC∶EMC=1∶1∶1, v / v solution of 1mol / L LiPF6 was used as the electrolyte, and a polypropylene microporous membrane was used as the separator to assemble a CR2016 simulated battery for subsequent testing. The constant current charge and discharge test of the button battery was carried out using the Xinwei company test system. The steps of the cycle performance test were: first activate it with a current of 0.05 C for one cycle, and then charge and discharge it for 400 cycles at a current of 0.5 C, and measure the change in electrode size and discharge specific capacity. The test results are shown in Table 1.

[0015] Embodiment 2:

[0016] A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 80W, the sputtering power of the graphite target is 80W, and the sputtering power of the copper target is 20W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then, the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 80W and 20W, and a 20nm thick Si layer is sputtered; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0017] Embodiment 3:

[0018] A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 90W, the sputtering power of the graphite target is 90W, and the sputtering power of the copper target is 25W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then, the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 90W and 25W, and a 20nm thick Si layer is sputtered; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0019] Comparative Example 1:

[0020] A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Then, a Si-graphene gradient alternating structure is prepared. The targets used are a silicon target with a purity of 99.999% and a graphite target with a purity of 99.99%. The sputtering power of the silicon target is 80W, and the sputtering power of the graphite target is 80W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then, the graphite target power is gradually reduced to 0W, and the silicon target sputtering power is gradually increased to 80W to sputter a 20nm thick Si layer; the graphite layer and the silicon layer multilayer structure are alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0021] Comparative Example 2:

[0022] A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are a silicon target with a purity of 99.999%, a graphite target with a purity of 99.999%, and a Cu target with a purity of 99.999%. The sputtering power of the silicon target is 80W, the sputtering power of the graphite target is 80W, and the sputtering power of the copper target is 20W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm, and then the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 80W and 20W, and a 20nm thick Si layer is sputtered; the graphite layer and the silicon layer multilayer structure are alternately deposited in the above manner, and a gradient transition is achieved, and finally an electrochemically enhanced battery electrode is obtained. The battery assembly and testing method refer to Example 1.

[0023] Comparative Example 3:

[0024] A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 80W, the sputtering power of the graphite target is 80W, and the sputtering power of the copper target is 20W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then the graphite target is turned off, and the silicon target and copper target are turned on with sputtering powers of 80W and 20W to sputter a 20nm thick Si layer; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0025] Comparative Example 4:

[0026] A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Then, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 80W, the sputtering power of the graphite target is 80W, and the sputtering power of the copper target is 10W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then, the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 80W and 10W to sputter a 20nm thick Si layer; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0027] Comparative Example 5:

[0028] A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 80W, the sputtering power of the graphite target is 80W, and the sputtering power of the copper target is 40W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then, the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 80W and 40W to sputter a 20nm thick Si layer; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0029] Table 1 Test results

[0030] .

Claims

1. A method for enhancing the electrochemical properties of a battery electrode, characterized in that: First, the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 8-12sccm; Subsequently, a Si-graphene gradient alternating structure is prepared, the sputtering power of the silicon target is 80-100W, the sputtering power of the graphite target is 80-100W, and the sputtering power of the copper target is 20-30W. At the initial stage of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 15-25nm, and then the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to a preset value to sputter a Si layer with a thickness of 15-25nm. In the above manner, a multilayer structure of graphite layers and silicon layers is alternately deposited, and a gradient transition is achieved; Finally, the alternating multilayer structure electrode was annealed, and the background vacuum degree was 3.0×10 -4 Pa, anneal at 300-400℃ for 20-30 minutes, and keep vacuum to cool naturally to room temperature after annealing.

2. The method according to claim 1, characterized in that The purity of the silicon target material used is 99.999%.

3. The method according to claim 1, characterized in that The purity of the graphite target used is 99.99%.

4. The method according to claim 1, characterized in that The purity of the Cu target material used is 99.999%.

5. The method according to claim 1, characterized in that The collecting fluid is PET, PP, PI or PC.

6. The method according to claim 1, characterized in that The current collector is cleaned and dried before being placed in the vacuum magnetron sputtering chamber.

7. A battery electrode improved by the enhancement method as claimed in claim 1.

8. The battery electrode according to claim 7, characterized in that The collecting fluid is PET, PP, PI or PC.

Citation Information

Patent Citations

  • Silicon-carbon thin film negative electrode material and preparation method thereof

    CN108807883A

  • Lithium ion battery silicon carbon film negative electrode material and preparation method thereof

    CN116344750A